Experimental investigation on the behavior of fly-ash based geopolymer reinforced concrete beams strengthened with CFRP - Ahmed S. Eisa; Mostafa H. Ahmed; Ivo Demjan; Dušan Katunský (Heliyon, 2023)
Recently, the demand for strengthening and rehabilitation of existing RC structures has increased due to the corrosion of internal steel reinforcement, variations in temperature, and increasing loading. As a result, several experimental studies have been performed to investigate the structural behaviour of strengthening RC beams with CFRP sheets, but few for GPC beams; therefore, this investigation focuses on the behaviour of strengthening GPC beams with CFRP sheets. In this experimental work, a set of ten specimen beams with the same cross section of 100 × 250 mm and 850 mm length with a 750 mm clear span were cast in two groups of five beams each. First group (flexural group) to study the flexural behavior, and the second one for the shear behaviour (shear group). In each group, the first beam was carried out as an RC control beam and the second as a GPC control beam without strengthening, while the other three beams were cast as GPC beams and strengthened with various schemes of CFRP sheets. All specimens were tested up to failure under two-sided static loading (four-point bending). The first cracking, yielding, and ultimate failure loads, the deflection values at midspan, the longitudinal bar strain, and the concrete strain were recorded for all tested specimens. The experimental results indicated that the Flextural Strengthening of GPC with CFRP sheet increased the First Cracking, yield and ultimate load capacity by 25.33%, 15.3% and 15% respectively, as well as, deflection was decreased by 16% on average while ductility and toughness have improved by 10% and 12% on average compared to R.C Beam.On the other side, the Shear Strengthening of GPC with CFRP strips increased the First Cracking, yield and ultimate load by 43%, 70% and 68% respectively, as well as, shear ductility has improved by 8% on average compared to R.C Beam. Overall, the different schemes of externally bound CFRP sheets have improved the flexural and shear behaviour of GPC beams.